ОСББ як форма громадської організації та його роль у житлово-комунальній реформі - Горбач, Олександр (Видавництво Львівської політехніки, 2019)
The article analyzes problems and prospects of housing and communal reform in Ukraine, the role of NGOs in the city development. The separate topic of the problems and perspectives of establishing and development of the the associations of the apartment house owners, their role in the sphere of housing and communal reforms.
Keywords: housing and communal reform; association of the apartment house owners; nongovernmental organizations; public participation; public budget